CHARACTER EDUCATION BASED ON MANHAJ OF THE SALAF AS SAALIH IN SALMAN AL-FARISI BOARDING SCHOOL KARANGANYAR IN 2016/2017 - Aziz, Tamim; Sugiyanto, Bayu Mufti (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
Character education based on Manhaj of the Salaf As-Saalih is the inculcation of Islamic values to a person or a group of people by imitating the attitude and behavior of the Salaf. The process is the effort to create ?perfect human? in the framework of self, family, community, and national development to provide contribution or positive influence on the world. This study is field research with a qualitative descriptive approach. It reveals that character education based on Manhaj of Salaf As-Saalih implemented in Salman Al-Farisi Boarding School is initiated since the acceptance of new students by identifying their ability and family background as the basis of the development strategy for the internalization of values incorporated in each program of school activities. The methods of targhib and tarhib as courtesy and morality control are the tool for students to motivate and practice their knowledge. Besides, the school stimulates and strengthens the characters through individual guidance by constructing good communication between teachers and students. The evaluation of learning output shows the achievement of cognitive or intellectual aspect in students, as well as effective aspect as indicated by several characters such as disciplined in attending the class and self-motivation to know and understand the conveyed material, which is closely related to the achievement of strengthening the student?s character. It can be concluded that character education based on Manhaj of the Salaf As-Saalih will contribute to realizing the goal of national education and in generating perfect humans who able to develop both themselves and the nation.